Chemical and Biological Investigations of Justicia gendarussa (Burm. f) - Uddin, Md Rakib; Sinha, Suchana; Hossain, Md Aslam; Kaisar, Md Abul; Hossain, Md Khalid; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In this study, three compounds, stigmasterol (1), lupeol (2), 16-hydroxylupeol (3) were isolated from the petroleum ether soluble fraction of a methanol extract of whole plant of Justica gendarussa (Burm. f). The crude methanol extract as well as its petroleum ether, carbon tetrachloride and chloroform soluble Kupchan fractions were studied for antioxidant, antimicrobial and cytotoxic activities. Among the different fractions tested for antioxidant activity, the chloroform soluble partitionate was the most potent with IC50 value of 18.80 μg/ml as compared to tertbutyl- 1-hydroxytoluene (IC50=17.69 μg/ml). Antimicrobial screening of the different extractives was conducted by the disc diffusion method and all the fractions except chloroform soluble partitionate exhibited mild antimicrobial activity with zone of inhibition ranging from 7-10 mm. In brine shrimp lethality bioassay, the petroleum ether soluble materials demonstrated the highest toxicity with LC50 of 1.27μg /ml. This is the first report of isolation of compounds from J. gendarussa, and its antioxidant, antimicrobial and cytotoxic properties. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10016 DUJPS 2011; 10(1): 53-57